Adaptation of introduced Robusta coffee clones in some agroclimate types in East Java. - Sugianto, Pingkan; Sudarsono, Sudarsono; Sukma, Dewi; Sumirat, Ucu (Indonesian Coffee and Cocoa Research Institute, 2022)
Indonesia is the fourth largest coffee producer in the world, even though it is not the original plant. Efforts to increase coffee genetic diversity in Indonesia through the results of the introduction are also carried out to improve the quality and quantity of coffee in the international market. The aim is to obtain robusta coffee clones that are able to adapt in several agroclimates in Indonesia and have stable yield potential, so that they can be cultivated extensively. The analytical method is AMMI biplot with six clones are FRT04, FRT06, FRT07, FRT09, FRT23, FRT65, and six locations are Bangelan, Kalibendo, Kaliselogiri, Gumitir, Malangsari, Silosanen.Then the agroclimate is suitable for widespread cultivation. The results of the study based on observations made on the production of coffee plants, which are climate types, which are somewhat wet and are getting good production results in the locations of Bangelan, Kaliselogiri and Silosanen. FRT07and FRT09 clones is the best clone of production and able to adapt, has interaction between locations with clones tested annually.